NUANSA ISLAMI PADA PENDIRIAN RUMAH ADAT BUGIS MAKASSAR MENURUT LONTARAQ - Irwan Abbas (Universitas Khairun, 2015)
These studies describe the tradition of building a custom home in BugisMakassar society. In Makassar Bugis society as in other indigenous peoples,building a home is not just to protect yourself from getting wet due to rain in therainy season, as well as shelter from the scorching heat of the sun in thedaytime and protect inhabitants from the cold night when darkness was eerie,but more of these functions are loaded with the content of philosophical values.The process of establishment of indigenous peoples Bugis Makassar startingfrom the selection of an appropriate place, the determination of the exact timeand day, the joint establishment of mutual cooperation, to the placement of anyarchitectural form, and the room has its own meaning and nuance. This studyproves humans since ancient local genius Bugis Makassar has an advantage indoing a job, including the establishment of a customs house through lengthyconsideration and accurate calculations. Thus the resulting work really satisfyworkers and residents who occupy it.